Future technology strategies for the geoscience sector: insights from STEEP and SWOT analyses - Bae, Si Woong; Lee, Jae-Wook (Frontiers in Earth Science, 2026)
Digital innovation technologies, such as artificial intelligence (AI), big data, and digital twins, are rapidly reshaping industries worldwide and fundamentally transforming traditional research and development (R&D) paradigms. The geoscience sector is no exception and must adapt through digitalization and intelligence-driven innovation to meet the demands of technological transformation. This study proposes future directions for technological development in geoscience. Comprehensive bibliometric and environmental analyses were conducted, covering domestic and international policies, market and industrial trends, and advancements in technology and R&D. Based on these findings, STEEP and SWOT analyses were applied to identify key challenges and strategic priorities. Four strategic directions have consistently emerged across the analytical frameworks: (1) advancement of AI and integration of AI agents, (2) development of resource exploration technologies for extreme environments to ensure future resource security, (3) expansion of intelligent climate technologies, and (4) creation of high-value-added services based on geoscience data. This study provides strategic insights to support digital transformation and sustainability in the geoscience sector, along with policy implications to enhance national resource security and global technological competitiveness.